2020
DOI: 10.3390/su12229779
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Characteristics of Metropolitan Areas on the Logistics Sprawl: A Case Study for Metropolitan Areas of the State of Paraná (Brazil)

Abstract: The concentration of warehouses in peripheral regions of metropolitan areas in a time period is called logistics sprawl (LS). Identifying this phenomenon could help to reduce externalities related to urban freight transport, mainly, the distance traveled. This paper examines the contribution of the characteristics of metropolitan areas on the logistics sprawl indicator. A case study was carried out considering data from eight metropolitan areas of the state of Paraná (Brazil). The research method is based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Regional distribution centers are mostly distributed in general cities and urban suburbs, and the spatial pattern of logistics enterprises shows significant characteristics of agglomeration and suburbanization. 5,6 Land rent, 7 transportation infrastructure, 8 market size, 9 population density, 10 urbanization level, 11 economic development level, 12 and policy influence 13,14 are the main factors affecting the spatial structure and diffusion of logistics enterprises 15,16 and location choice. 17,18 With the widespread application of information technologies such as blockchain [19][20][21] and the Internet of Things (IOT) [22][23][24][25] in research, the use of big data for research is increasing, which enriches research methods and expands research fields.…”
Section: Introductionmentioning
confidence: 99%
“…Regional distribution centers are mostly distributed in general cities and urban suburbs, and the spatial pattern of logistics enterprises shows significant characteristics of agglomeration and suburbanization. 5,6 Land rent, 7 transportation infrastructure, 8 market size, 9 population density, 10 urbanization level, 11 economic development level, 12 and policy influence 13,14 are the main factors affecting the spatial structure and diffusion of logistics enterprises 15,16 and location choice. 17,18 With the widespread application of information technologies such as blockchain [19][20][21] and the Internet of Things (IOT) [22][23][24][25] in research, the use of big data for research is increasing, which enriches research methods and expands research fields.…”
Section: Introductionmentioning
confidence: 99%
“…In an empirical analysis, Heitz et al (2020) revealed that the accessibility and availability of transport infrastructure attract warehouses in Gothenburg metropolitan area. Sousa and Oliveira (2020) showed the size of the metropolitan area in square meters, the number of cities and the retail business in luences the concentration of warehouses in metropolitan areas of Paraná State, in Brazil. More recently, and using spatial analysis, Guerin et al (2021) identi ied the municipalities with the concentration of warehouse per capita are surrounded by the high occurrence of cargo theft, high road extension, high land cost, and leet in the Metropolitan Area of São Paulo.…”
Section: Introductionmentioning
confidence: 99%